(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
Palm kernel cake (PKC), a by-product of the palm oil industry is limited in its use as a feedÂ ingredient for poultry due to its high fibre and lignin content. The presence of these antinutritiveÂ components is the result of shells contaminating the by-product. The nutritive value ofÂ PKC has to be improved in order to increase its inclusion rate in poultry diet. In this study, PKCÂ was subjected to a separation method using static cling and electrostatic separation to remove the shells present in PKC. Response surface methodology based on Box-Behnken design wasÂ used to optimize the separation method with moisture content (8 to 18%), particle sizeÂ distribution (0.5 to 2.5 mm) and feed rate (20 to 200 g/min) as the independent variablesÂ evaluated. According to the regression coefficients and significance of the quadratic polynomialÂ model, the optimum separation parameters were as follows: 13% PKC moisture content; <1.5 mm PKC particle size and 110 g/min feed rate. Under these conditions, the total lignin contentÂ of PKC was reduced to 8.1% PKC and crude fibre to 10.2%.